2007
DOI: 10.1093/tropej/fmm007
|View full text |Cite
|
Sign up to set email alerts
|

National Vitamin A Supplementation Coverage Survey among 6-59 Months Old Children in Guinea (West Africa)

Abstract: In order to increase overall VAS coverage and reduce regional disparities, it is suggested that mass VAS be organized on a regional level, prioritizing rural regions (Middle and Upper Guinea) and the city of Conakry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 3 publications
8
37
1
Order By: Relevance
“…Also, this present study indicates that the father's occupation is not in any way protective for receipt of VAC supplement, as children whose fathers were manual workers were less likely to receive VAC supplement compared to those whose fathers were not working. Furthermore, our results show that there is wide variation in uptake of VAC supplement by children across all the geographical regions in Nigeria; this finding is similar to those obtained in another western African country [57]. Specifically, the results show that despite the reported high prevalence of VAD, which is higher than the national average in the North West geographical region [19], children in this region are less likely to have received VAC supplement.…”
Section: Discussionsupporting
confidence: 86%
“…Also, this present study indicates that the father's occupation is not in any way protective for receipt of VAC supplement, as children whose fathers were manual workers were less likely to receive VAC supplement compared to those whose fathers were not working. Furthermore, our results show that there is wide variation in uptake of VAC supplement by children across all the geographical regions in Nigeria; this finding is similar to those obtained in another western African country [57]. Specifically, the results show that despite the reported high prevalence of VAD, which is higher than the national average in the North West geographical region [19], children in this region are less likely to have received VAC supplement.…”
Section: Discussionsupporting
confidence: 86%
“…Our analysis showed that parental education is an important predictor of compliance with the VAS program, a finding that corroborates the results of a pooled data analysis in African settings [14]. A literature review has revealed any implementation of a door-to-door supplementation program resulting in universal visiting of households by the health work force may nullify the negative impact of paternal illiteracy [15]. Illiterate parents fail to understand the important health impacts of VAS, and thus they are less motivated to participate in the supplementation program.…”
Section: Discussionsupporting
confidence: 87%
“…We did not find any difference in recipient status of VAS among male and female children, indicating a lack of gender inequity in VAS attendance. Similar findings have been reported from studies in India, Nepal and countries in Africa [14,15]. A study in Bangladesh and another one in the Philippines reported similar coverage patterns of VAS in male and female children [20,21].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…10,12,18 Another study mentions education as an important factor in the distribution of vitamin A capsules. Children with parents who only had primary school education or lower had a higher risk of not receiving the vitamin A capsule compared to those with parents who had at least junior high school education.…”
mentioning
confidence: 99%